Investigation of Bisphenol A as an endocrine disruptor, total thiol, malondialdehyde, and C-reactive protein levels in chronic obstructive pulmonary disease - Erden, E S; Motor, S; Ustun, I; Demirkose, M; Yuksel, R; Okur, R; Oktar, S; Yakar, Y; Sungur, S; Gokce, C (European review for medical and pharmacological sciences, 2014)
Chronic obstructive pulmonary disease (COPD) is a common health problem and it is associated with oxidant/antioxidant imbalance and systemic inflammation. Bisphenol A (BPA) is an endocrine disruptor agent, exerting a wide variety of metabolic effects. Also, BPA is related with oxidative stress, decreased antioxidant enzymes, and inflammation. The aim of this study is to investigate the relationships between COPD and serum BPA, C-reactive protein (CRP), malondialdehyde (MDA), and total thiol levels. This study was enrolled at 83 subjects that they were divided into two groups: control (n=33), COPD (n=50). The serum BPA, CRP, MDA, and total thiol levels were analyzed. The CRP and BPA levels were significantly higher in the COPD patients than control subjects. The total thiol levels were significantly lower in COPD cases than the controls. There is no different between groups for MDA. Also, there had a linear relationship between BPA and CRP in correlation analysis. COPD is associated with high serum BPA, CRP and low total thiol levels in comparison with healthy individuals. It is suggested that BPA might have a role in the etiopathogenesis of COPD.